Exploring Family-Owned SMEs: A Systematic Review of Corporate Social Responsibility Practices - Mugi Harsono; Eni Munarsih; Ratya Syafira Arifiani; Wahyu Hidayat (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Objective: This study explores how family values are reflected in the Corporate Social Responsibility (CSR) practices of family owned small- and medium-sized enterprises (SMEs). It also seeks to identify the dominant theoretical frameworks and conceptual models used in CSR research on these firms. This study addresses a gap in the literature by focusing specifically on SMEs, which have been underrepresented in systematic reviews of CSR in family businesses. Research Design & Methods: A systematic literature review (SLR) was conducted following the PRISMA 2020 guidelines. A comprehensive database search identified 418 articles that were initially screened based on clearly defined inclusion and exclusion criteria. After a multi-stage review process, 55 articles were selected for analysis. This study employed thematic analysis to categorize CSR motivations, practices, and outcomes in family-owned SMEs. Findings: Findings indicate that CSR in family-owned SMEs is strongly shaped by informal mechanisms, community embeddedness, and intergenerational values. Socioemotional wealth (SEW) and stewardship theories are the most frequently applied frameworks. However, CSR initiatives in these firms are typically reactive and value-driven, rather than strategic. Variations were found across contexts, with firms in developing countries being more influenced by family legacy and community ties. Implications & Recommendations: This study highlights the need for tailored CSR frameworks that consider the informal nature and resource limitations of family-owned SMEs. Policymakers and support institutions should design CSR programs that align with these firms’ values and structures. Future research should explore the longitudinal changes in CSR motivations as family firms evolve across generations. Contribution & Value Added: This study contributes to the CSR and family business literature by focusing on how CSR is practiced and theorized within family-owned SMEs. It differentiates itself from prior reviews by concentrating on smaller enterprises and uncovering unique CSR patterns tied to family dynamics and informal governance structures.